Cataract in the Eye: The Effect of Religious Practitioners on the Socio-Economic and Ethno-Religious Conflicts in Market Places in Lagos, Nigeria - Omojuwa, Ayodele (NIU Journal of Humanities; Vol 6 No 1 (2021): KIU Journal of Humanities, Vol. 6 No. 1, March 2021, 2021)
This study examines the ethno religious conflict effects on the local market of Lagos State, Nigeria with a view toward determining its role the two major religion (Christianity and Islam) in the lives of marketer and people  in the market and the community. The paper relies on both primary and secondary sources including a structure research questionnaire, books, journals and magazines that deal with religious conflicts and crises in Nigeria. Intractable conflict and political economy theories are blended in our analysis. We argue that inter-religious conflicts in Nigeria defy resolutions and seem unending because they are intractable conflicts, which are sustained largely because they serve the economic interest of certain religious leaders who conceal the economic matrix behind their support. This work recommends that increased awareness should be created to enlighten people on the dangers of these crises in the market place. We suggest government strive to provide laws to protect all citizens against ethno-religious crises. Finally, religious leaders should preach and teach to increase national unity, purity, tolerance, morality, love and honesty to reduce conflicts among religious groups, thereby uniting through dialogue for national development.